Cysteinyl leukotriene correlated with 8-isoprostane levels as predictive biomarkers for sensory dysfunction in autism. Issue 1 (December 2016) - Qasem, Hanan; Al-Ayadhi, Laila; El-Ansary, Afaf
Abstract Background Autism is a neurodevelopmental disorder that clinically presented as cognitive deficits, social impairments and sensory dysfunction. An increasing body of evidence has shown that oxidative stress and inflammation are involved in the pathophysiology of autism. Recording biomarkers as measure of the severity of autistic features might help in understanding the pathophysiology of autism. Methods This study investigates the plasma levels of 8-isoprostane and Cysteinyl leukotrienes (CysLTs) in 44 autistic children and 40 healthy controls. The recruited autistic patients were assessed for behavior, cognitive and sensory deficits by using different autism severity rating scales, including the Childhood Autism Rating Scales (CARS), Social responsiveness scale (SRS) and Short Sensory Profile (SSP). Receiver Operating Characteristics analysis (ROC) of the obtained data was performed to measure the predictive value of 8-isoprostane and Cysteinyl leukotrienes (CysLTs) as oxidative stress- related parameters. Pearson's correlations between the measured parameters was also performed. Results The concentrations of 8-isoprostane and CysLTs in autistic patients were significantly higher than those in controls. While cognitive and social impairments did not show any significant differences, the SSP results were strongly correlated with the levels of both of the biomarkers assessed. However, autistic children showed improvements in oxidative stress status (as determined by 8-isoprostane levels) at increasing ages. Conclusion This study indicates that 8-isoprostane and CysLTs can be used as markers for the early recognition of autistic patients through sensory deficits phenotypes which might help early intervention.